National report on the status of women in the Bahamas 1994 (The Ministry [Nassau]BS, 1994)
Reviews and appraises the status of women at the national level. Looks at international technical cooperation, strategic goals and objectives.
Prepared for United Nations Fourth World Conference on Women, Beijing, China, September 1995.